Efficiency Predictive Factors for Professional Ability of Ramkhamhaeng University Lecturers for ASEAN Socio-Cultural Community - Cruthaka, Chomsupak; Chancharoen, Duangduen; Tungprapa, Taviga; Ingard, Apinya; Suksod, Pornkul (Asian Journal of Education and Training, 2020)
This study aims to investigate the relationship between the use of information technology for retrieval and communication ability; intercultural learning ability; English ability and interpersonal ability with professional ability of Ramkhamhaeng University (RU) lecturers for ASEAN socio-cultural community (ASCC); and study the efficiency predictive factors of professional ability of RU lecturers for ASCC. The sample population consisting of 295 RU lecturers. The instrument of research was a five-rating scale questionnaire eliciting data concerning the predictive factors of professional ability of RU lecturers for ASCC. The questionnaires were tested for content validity index and the reliability by Cronbach’s alpha coefficient were .91, .95, .85, .95 and .96 respectively. Data were analyzed by frequency, percentage, mean, standard deviation, Person product moment correlation and stepwise multiple regression analysis. Findings: 1. Interpersonal ability; English ability; intercultural learning ability; and the use of information technology for retrieval and communication ability were a positive moderate correlation and the professional ability with statistical significance at the level of .01. (r=338, .415, .449 and .444) 2. The use of information technology for retrieval and communication ability (X1); intercultural learning ability (X2) and English ability (X3 ) were to predicted professional ability of RU lecturers for ASCC account to 52.70 percent (Adjusted R2 =.527). The predicted in row score equation as follows: Y’ = 1.068 + .332(X1) + .244(X2) + .194(X3) The predicted in standardized equation as follows: Zy’ = .359(Zx1) + .279(Zx2) + .244(Zx3).